Development of Wound Dressing Hydrogel Based Combination of Cassava Starch/PVA and Aloe Vera Extract: Hydrogel-based combination of cassava starch/PVA/Aloe vera extract - Zai, Khadijah; Dwi Utami, Arini Hastin (Iranian Journal of Pharmaceutical Sciences, 2025)
Wound care involves various methods, including dressing to prevent bacterial infection at the wound site. Typically, these dressings are made from synthetic materials lacking biocompatibility. Many researchers have explored alternative wound dressings derived from natural polymers due to their non-toxic, biocompatible properties and natural degradation, such as starch. However, starch exhibits low mechanical strength, necessitating its combination with other polymers. Additionally, high-quality wound dressings require additional components that can expedite wound healing. Therefore, this study aims to develop a hydrogel-based wound dressing using a combination of cassava starch, polyvinyl alcohol (PVA), and aloe vera extract. The simplex lattice design (SLD) determined the optimal hydrogel film formula. A comprehensive examination was conducted, encompassing a multitude of parameters; including pH value, swelling index ratio, degradation ratio, and water vapor transmission rate (WVTR). The ideal formula comprised 5% cassava starch, 5% PVA, and 2% aloe vera extract. Characteristics included a swelling ratio of 399.33 ± 33.13% and WVTR of 816.13±87.72 g/m2 day, film degradation of 85.93 ± 0.1% after 14 days, pH of 5.88 ± 0.22, and tensile strength of 17.92 ± 12.80 MPa, with a transparent and slightly yellowish appearance. This optimal hydrogel film showed promise as a wound dressing alternative.